Advantages and Disadvantages of Social Media Marketing - Agarwal, Varsha (IJARESM, 2022)
The aim of the research is to determine the advantages and disadvantages of social media marketing.The benefits and drawbacks of social media marketing are discovered and compared.Knowing the advantages and disadvantages of social media marketing is vital for businesses as they get to know all the risks and benefits involved in it. Consumers and buyers are already utilizing social media platforms for online buying, but they must be made aware of the possible risks and drawbacks.Marketers need to get on the trend of social media marketing as most of their customers spend a lot of time on social media. It's a free marketing space for them to indulge into and it's a great way to connect with potential customers in a personalized way.Given the status of the economy, entrepreneurs must learn how to use social media to increase advertising and improve marketing.Various articles, journals and websites were visited to gather information about the topic.In the end the paper concludes with determining whether the advantages outweigh the disadvantages.
ISME
Keywords: Social Media Marketing; Advantages; Disadvantages; Business Marketing; Advertising